Approximation by modified q‐Gamma type operators in a polynomial weighted space. (30th August 2022) - Singh, Jitendra Kumar; Agrawal, Purshottam Narain; Kajla, Arun
Abstract : In this research article, we construct a q $$ q $$ ‐analogue of the operators defined by Betus and Usta (2020) and study approximation properties of these operators in a polynomial weighted space. Further, we modify these operators to study the approximation properties for differentiable functions in the same space and show that the modified operators give a better rate of convergence.